Analysis of process parameters for a surface-grinding process based on the Taguchi method - Külekci, Mustafa Kemal (Materiali in tehnologije, 2013)
In this study, the Taguchi method that is a powerful tool to design optimization for quality is used to find the optimum surface roughness in grinding operations. An orthogonal array, a signal-to-noise (S/N) ratio, and an analysis of variance (ANOVA) are employed to investigate the surface-roughness characteristics of AISI 1040 steel plates using EKR46K grinding wheels. Through this study, not only can the optimum surface roughness for grinding operations be obtained, but the main grinding parameters affecting the performance of grinding operations can also be found. Experimental results are provided to confirm the effectiveness of this approach. The results of this study showed that the depth of cut and the wheel speed have significant effects on the surface roughness, while the rate of feed has a lower effect on it.
Keywords: brušenje; površine; Taguchijeva metoda; hrapavost